1996
DOI: 10.1128/jvi.70.7.4854-4857.1996
|View full text |Cite
|
Sign up to set email alerts
|

Sequence determinants of 3A-mediated resistance to enviroxime in rhinoviruses and enteroviruses

Abstract: Using site-directed mutagenesis of the 3A coding region of rhinovirus 14, we have expanded our analysis of resistance to enviroxime. We have observed that high and low levels of drug resistance involve two domains within 3A and that the amino acid at position 30 is critical in determining resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 16 publications
(18 reference statements)
0
21
0
Order By: Relevance
“…Interestingly, a single point mutation in the viral protein 3A can bypass the need of CVB3 for PI4KIIIβ without affecting its virulence (Thibaut et al, 2014;van der Schaar et al, 2012). This mutation has been identified earlier as resistance mutation against enviroxime, a small molecule drug inhibiting replication of different positive-strand RNA viruses like PV, CVB3 and rhinoviruses (Heinz and Vance, 1996). However, it also confers cross-resistance to other inhibitors like PIK93, which efficiently targets PI4KIIIβ (Borawski et al, 2009), or to direct knockdown of PI4KIIIβ.…”
Section: Lipid-modifying Enzymes and Transportersmentioning
confidence: 99%
“…Interestingly, a single point mutation in the viral protein 3A can bypass the need of CVB3 for PI4KIIIβ without affecting its virulence (Thibaut et al, 2014;van der Schaar et al, 2012). This mutation has been identified earlier as resistance mutation against enviroxime, a small molecule drug inhibiting replication of different positive-strand RNA viruses like PV, CVB3 and rhinoviruses (Heinz and Vance, 1996). However, it also confers cross-resistance to other inhibitors like PIK93, which efficiently targets PI4KIIIβ (Borawski et al, 2009), or to direct knockdown of PI4KIIIβ.…”
Section: Lipid-modifying Enzymes and Transportersmentioning
confidence: 99%
“…The amino acid differences responsible for the rhodanine-resistant phenotype have not yet been identified. Similarly, resistance to enviroxime, an inhibitor of picornavirus RNA replication, has been mapped to the 3A protein, and amino acid substitutions conferring resistance have been mapped for human rhinovirus 14, PV 1 (158), and CBV 3 (159). If clinically useful antiviral agents were identified, it would be necessary to monitor drug resistance.…”
Section: Determination Of Sensitivity or Resistancementioning
confidence: 99%
“…Surprisingly, no shift in antiviral potency was seen in the comparison of wild-type viruses to mutant viruses in the regular HRV CPE-based assay. Published data suggested that the mutations that seemed to confer resistance to enviroxime did not confer a very high resistance level (41). In order to assess the resistance potency of the mutation, a different approach was taken.…”
Section: Screening Of a Diverse Subset Of The Proprietary Collection mentioning
confidence: 99%